Pemidanaan Terhadap Pelaku Penangkapan Ikan dengan Penggunaan Bahan Peledak - I Wayan Agus Andika; I Made Minggu Widyantara; I Nyoman Sutama (Fakultas Hukum, Universitas Warmadewa, 2021)
The fishing that is carried out will have a bad effect on the marine ecosystem, but great benefits can be obtained for the fishermen. Catching fish using explosives is a criminal act in the field of fisheries and such actions may be subject to sanctions as regulated in Law Number 45 of 2009 concerning Fisheries and the Emergency Law on firearms. This study examines legal arrangements regarding the use of explosives in fishing and reveals criminal sanctions against perpetrators of catching fish with the use of explosives. The method used is normative legal research with a statutory approach. The data sources used are primary and secondary data obtained through recording and documentation techniques, then the data is processed by legal interpretation. The results of the study revealed that the legal rules regarding fishing carried out using a hazardous material or explosives have been regulated in Law Number 45 of 2009 concerning Fisheries and the Emergency Law concerning explosives and firearms. Criminal sanctions that can be applied to perpetrators are regulated in Article 84 paragraph (1) to paragraph (4) of Law Number 45 of 2009 concerning Fisheries.